Lesson Study as a Means of Reflection and Improving the Quality of Teaching Practices - Damayanti, Sri; Akib, Erwin; Satriana, Eny (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Despite its critical role in improving learning, the quality of teaching practices often stagnates due to the limited use of systematic reflective approaches among educators. This study investigates Lesson Study as a structured model to enhance reflective teaching and strengthen instructional quality through a qualitative descriptive-analytical literature review. This paper synthesizes findings from more than 50 scholarly sources, including Scopus-indexed articles, SINTA-accredited national journals, conference proceedings, and institutional reports from OECD, UNESCO, and the World Bank, published between 2010 and 2025. Through a systematic search using keywords related to “Lesson Study” and “teaching reflection,” data were analyzed thematically with the support of NVivo. The review offers an integrated synthesis of how Lesson Study contributes to teaching effectiveness, professional teacher reflection, and student learning, while also mapping contextual barriers within the Indonesian education system. Findings indicate that Lesson Study can enhance teaching effectiveness through the plan–do–see–reflect cycle, foster a culture of professional reflection, and support gains in student learning outcomes, although its implementation in Indonesia remains inconsistent due to time limitations, administrative demands, and hierarchical work culture. Results further suggest that Lesson Study may be more effective than workshops or individual self-evaluation because of its collaborative and evidence-based nature. To strengthen sustainability, strategies include alignment with the Guru Penggerak program, dedicated reflection time, and the development of cross-school professional communities. Overall, this review highlights the potential of Lesson Study to support long-term improvement in teaching quality and contribute to the achievement of SDG 4 in Indonesia.